Physics and Chemical Method of Obtaining Extraction Phosphate Acid - Oribjonov Jamshid Xayrullo oʻgʻli (European Science Publishing, 2023)
To obtain phosphate acid, natural phosphorites are affected by sulfuric acid in concentrates Ca5(PO4)3F + 5H2SO4 + 5nH2O = 5CaSO40nH2O + 3H3PO4 + HF and in the next step, the method based on the extraction of sulfuric acid from the liquid phase is called an extraction or wet method. The resulting product is referred to as extraction phosphate acid (EFK). From the resulting phosphate acid, a variety of phosphorite fertilizers are developed. The main condition for the implementation of the process of acid extraction of sulfuric acid is the extraction of crystals from phosphate acid that are large enough of calcium sulphate, easily separated and well washed.